The Studentsâ€™ Reading Competence in Recount Text: A Study on the Ninth Grade Students of SMP Bustanul Ulum Bantarkawung - M Mujiburrohman (Jurnal Kependidikan, 2020)
The research aim to measure the studentsâ€™ reading competence in using Recount Text tense. The reading skill became very important in the education field, students need to be exercised and trained in order to have a good reading skill. The research was descriptive quantitative method. The writer had been conducted on September 2013 and The subject of this research was the Eighth Grade students of SMP Bustanul ulum Bantarkawung, Brebes in the Academic year 2012/2013. The sample was 41 students of 82 Students, consisting of 41 from class VIII A and 41 students from class VIII B. In collecting data, the writer used a subjective test which consisted of 20 items, all the items were multiple choice test. After conducting the research, it revealed that the mean of the studentsâ€™ reading competence in using Recount Text tense was 78. It means that the average of the students could answer 61-80%% of the test items correctly. It indicated that the studentsâ€™ reading competence in using Recount Text belonged to â€œgoodâ€ category. The finding of the research had been contribution to reading competence education in SMP Bustanul Ulum Bantarkawung. The English teacher could get some different ways to improve the studentsâ€™ reading competence.